"1, 000 conversations I'd rather have than that one:" A qualitative study of prescriber experiences with opioids and the impact of a prescription drug monitoring program. Issue 4 (3rd October 2022) - Zavodnick, Jillian; Wickersham, Alexis; Petok, Alison; Worster, Brooke; Leader, Amy
Abstract: Background: Prescription Drug Monitoring Programs (PDMPs) have shown impacts on a number of opioid-related outcomes but their role in clinician emotional experience of opioid prescribing has not been studied. Objectives: This study explores the impact of PDMPs on clinician attitudes toward and comfort with opioid prescribing, their satisfaction with patient interactions involving discussion of opioid prescriptions, and their recognition of opioid use disorder (OUD) and ability to refer patients to treatment. Methods: Researchers conducted semi-structured interviews with five physicians and two nurse practitioners from a variety of specialties and practice environments. Results: Many participants reported negative emotions surrounding opioid-related patient encounters, with decreased anxiety related to PDMP availability. These effects were less pronounced with clinicians who had greater opioid prescribing experience (either longer careers or higher-volume pain practices). Many participants felt uncomfortable around opioid prescribing. Data from the PDMP often changed prescribing practices, sometimes leading to greater comfort writing a prescription that might have felt riskier without PDMP data. Clinicians easily recognized patient behaviors, symptoms, and prescription requests suggesting that opioid-related adverse events were accumulating, but did not usually apply a label of OUD to these situations. PDMP findings occasionally contributed to a diagnosis and treatment referral for OUD. Conclusions: PDMP data is part of a nuanced approach to prescribing opioids. The objectivity of the data may be helpful in mitigating clinician negative emotions that are common around opioid therapy.